V2: Integrated management of rainwater for crop-livestock agroecosystems - Ayantunde, Augustine A.; Puskur, Ranjitha; Gerard, Bruno G.; Valbuena, Diego; Asse, Rainer (2010)
With mixed crop-livestock systems projected to remain the main providers of food in the coming decades, opportunities exist for smallholders to participate and benefit from emerging crop and livestock markets in the Volta Basin. This project intends to identify, evaluate, adapt, and disseminate best-fit integrated rainwater management strategies (RMS), targeted to different biophysical and socio-economic domains. The integrated RMS are comprised of technological solutions, directed at different components of the agroecosystems, underpinned by enabling institutional and policy environments and linked to market incentives that can drive adoption